Faktor-Faktor Yang Mempengaruhi Pemanfaatan Program Pos Pembinaan TerpaduPenyakit Tidak Menular Di Wilayah Kerja Puskesmas Batang Toru KabupatenTapanuli Selatan Tahun 2017 - Tanjung, Wiwi Wardani; Harahap, Yanna Wari; Panggabean, Meilina Sari (Universitas Aufa Royhan, 2018)
Strategic Plan 2015-2019 of the Ministry of Health Posbindu activities PTM minimum target is 20% of the population aged 15 years and above in the relevant area. PTM Posbindu visit coverage in Puskesmas Batang Toru low at 0.2%. Based on the preliminary survey has been conducted Posbindu program still experiencing problems. Less or at least the number of visits ages 15-44 who utilize health services. The presence of the participants did not routinely every month, ignorance of society to benefit Posbindu. The purpose of this study to analyze the factors - factors that affect the utilization of the Integrated Development of Post Communicable Diseases (Posbindu PTM) in Puskesmas Batang Toru Tapanuli Selatan Year 2017. This type of research is explanatory research with cross sectional study population in this study group of healthy people, risk and people with non-communicable diseases aged 15- 44 years in 10 Posbindu PTM amounted to 10,384 people, while the sample in this study using the technique of cluster sampling area amounted to 99 people. Data were collected through interviews using questionnaires, the data were analyzed using univariate, bivariate and multivariate analyzes. Based on the statistical test result with chi-square test, there is a relationship of predisposing factors such as age (0.000 <0.05), gender (0.028 <0.05), education (0.043 <0.05), employment (0.002 <0.05 ), knowledge (0.0002 <0.05), attitude (0.007 <0.05), perception (0.001 <0.05). There is a relationship that health facilities enabling factor (0.001 <0.05), health professionals (0.018 <0.05), volunteers (0.000 <0.05). In conclusion, there is the influence of predisposing factors (education, work, knowledge, attitudes, perceptions) and enabling factors (health workers and volunteers) on the utilization of the integrated development post non-communicable diseases. Age, gender and health facilities have no effect on the utilization of the integrated development post noncommunicable diseases. It suggested for Posbindu need to do counseling about the benefits Posbindu follow the activities of non-communicable diseases.